How accurate is digital-assisted Le Fort I maxillary osteotomy? A three-dimensional perspective. Issue 1 (January 2020) - Mulier, D.; Shaheen, E.; Shujaat, S.; Fieuws, S.; Jacobs, R.; Politis, C.
Abstract: The aim of this study was to evaluate the surgical accuracy of Le Fort I surgery compared to the three-dimensional (3D) virtual planning. Fifty-five patients (29 males, 26 females; age range 15–58 years) with skeletal class III malocclusion, who underwent bimaxillary surgery were included. A validated 3D accuracy assessment tool was utilized to assess the surgical accuracy of the maxillary positioning. For translational movements, the least amount of error was associated with mediolateral translation, whereas the surgical accuracy for anteroposterior and superoinferior translation showed a tendency towards a more posterior and inferior positioning of the maxilla compared to the planning. For rotational movements, the highest discrepancy was observed for pitch. Linear regression showed increased inaccuracy with increasing advancement for anteroposterior, superoinferior and pitch movements. To conclude, 3D virtual planning of maxilla was generally accurate when compared to achieved outcome for skeletal class III patients undergoing bimaxillary surgery.